18β-Glycyrrhetinic Acid Protects against Cholestatic Liver Injury in Bile Duct-Ligated Rats - Pin-Ho Pan; Ya-Yu Wang; Shih-Yi Lin; Su-Lan Liao; Yu-Fang Chen; Wei-Chi Huang; Chun-Jung Chen; Wen-Ying Chen (MDPI AG, 2022)
18β-Glycyrrhetinic acid is a nutraceutical agent with promising hepatoprotective effects. Its protective mechanisms against cholestatic liver injury were further investigated in a rodent model of extrahepatic cholestasis caused by Bile Duct Ligation (BDL) in rats. The daily oral administration of 18β-Glycyrrhetinic acid improved liver histology, serum biochemicals, ductular reaction, oxidative stress, inflammation, apoptosis, impaired autophagy, and fibrosis. 18β-Glycyrrhetinic acid alleviated the BDL-induced hepatic and systemic retention of bile acids, matrix-producing cell activation, hepatic collagen deposition, Transforming Growth Factor beta-1/Smad activation, malondialdehyde elevation, glutathione reduction, High Mobility Group Box-1/Toll-Like Receptor-4 activation, NF-κB activation, inflammatory cell infiltration/accumulation, Interleukin-1β expression, Signal Transducer and Activator of Transcription-1 activation, Endoplasmic Reticulum stress, impairment autophagy, and caspase 3 activation. Conversely, the protein expression of Sirt1, Farnesoid X Receptor, nuclear NF-E2-Related Factor-2, Transcription Factor EB, bile acid efflux transporters, and LC3-II, as well as the protein phosphorylation of AMP-Activated Protein Kinase, was promoted in 18β-Glycyrrhetinic acid-treated BDL rats. The hepatoprotective effects of 18β-Glycyrrhetinic acid in the present investigation correlated well with co-activation and possible interactions among Sirt, FXR, and Nrf2. The concurrent or concomitant activation of Sirt1, FXR, and Nrf2 not only restored the homeostatic regulation of bile acid metabolism, but also alleviated oxidative stress, inflammation, apoptosis, impaired autophagy, and fibrosis.